2008 41st IEEE/ACM International Symposium on Microarchitecture 2008
DOI: 10.1109/micro.2008.4771797
|View full text |Cite
|
Sign up to set email alerts
|

CPR: Composable performance regression for scalable multiprocessor models

Abstract: Uniprocessor simulators track resource utilization cycle by cycle to estimate performance. Multiprocessor simulators, however, must account for synchronization events that increase the cost of every cycle simulated and shared resource contention that increases the total number of cycles simulated. These effects cause multiprocessor simulation times to scale superlinearly with the number of cores.Composable performance regression (CPR) fundamentally addresses these intractable multiprocessor simulation times, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…Performance models have been increasingly used for application tuning over complex or large scale systems [3], [12], [17]. These models target performance over a cluster or a heterogeneous platform, with a focus on the modeling and optimization of communication and scheduling among nodes.…”
Section: Related Workmentioning
confidence: 99%
“…Performance models have been increasingly used for application tuning over complex or large scale systems [3], [12], [17]. These models target performance over a cluster or a heterogeneous platform, with a focus on the modeling and optimization of communication and scheduling among nodes.…”
Section: Related Workmentioning
confidence: 99%
“…Models for microprocessor cores and mechanisms to account for interactions would provide a more thorough assessment of multiprocessor performance and power. Building on uniprocessor core models, a potential multiprocessor framework might use a combination of uniprocessor, contention, and penalty models [Lee et al 2008].…”
Section: Discussionmentioning
confidence: 99%
“…The SDCs serve as input to a cache contention model that estimates the additional number of conflict misses due to cache sharing in the LLC. There exist several cache contention models [Chandra et al 2005;Eklöv et al 2011;Lee et al 2008]. We use the Frequency of Access (FOA) model proposed by Chandra et al [2005] because it is a fairly simple model and we found it accurate enough for our needs.…”
Section: Iterative Multicore Performance Estimationmentioning
confidence: 99%